A cost of living index incorporating a network effect - Madden, Gary; Coble-Neal, Grant (Routledge, 2004)
This paper constructs a cost of living index (COLI) that incorporates a networkeffect. While in this instance the application is to the telecommunications sector,the COLI are applicable more generally to network industries. The COLI permitvalid welfare comparisons to be made by individual, region and country. IllustrativeCOLI estimates are provided for selected OECD member country telecommunicationsmarket data.